Language and content complexities encountered by students in taxation courses / Loo Ern Chen and Ho Juan Keng - Loo, Ern Chen; Ho, Juan Keng (Faculty of Accountancy, 2004)
Courses in taxation generally cover elements pertaining to the quantitative, legal and expository aspects, all of which rely on the understanding and interpretation of complex tax statutes, which in turn involve both language and content complexities. This study is on students pursuing taxation courses at the tertiary level in Malaysia, where the medium of instruction is in English, which is neither the students' mother tongue nor their first language. As tax statutes and reference materials on taxation in Malaysia are mainly in English, and taxation courses are taught and assessed in English, a reasonably high level of English language skills is essential to cope with the legal and expository aspects. The study reveals that a majority of the students agreed that they encountered difficulties in terms of language complexity rather than content complexity, particularly in relation to understanding textbooks and examination questions. In terms of content complexity, less than one third agreed that they encountered difficulties in understanding textbooks and lectures / tutorials.